Combined numerical and experimental studies of 21700 lithium-ion battery thermal runaway induced by different thermal abuse. (15th September 2022) - Shelkea, Ashish V.; Buston, Jonathan E.H.; Gill, Jason; Howard, Daniel; Williams, Rhiannon C.E.; Read, Elliott; Abaza, Ahmed; Cooper, Brian; Richards, Philp; Wen, Jennifer X.
Highlights: Developed a CFD approach for heating induced thermal runaway incorporating heat dissipation. Predictions established the critical temperature to trigger TR for the current LIB as 131–132  ° C. Filled important experimental gaps on heat generation of the different decomposition reactions. Analysis demonstrates effective prevention of TR propagation needs to be implemented prior to TR. Abstract: Combined numerical and experimental studies have been carried out to investigate thermal runaway (TR) of large format 21700 cylindrical lithium-ion battery (LIB) induced by different thermal abuse. Experiments were firstly conducted with the Extend Volume Accelerating Calorimetry (EV-ARC) using both the heat-wait-seek (HWS) protocol and under isothermal conditions. The kinetic parameters were derived from one of the HWS EV-ARC tests and implemented in the in-house modified computational fluid dynamics (CFD) code OpenFOAM. For the subsequent CFD simulations, the cell was treated as a 3-D block with anisotropic thermal conductivities. The model was verified by the remaining two HWS tests not used in the derivation of the kinetic parameters and validated with newly conducted isothermal EV-ARC tests. Further laboratory tests and model validation were also subsequently conducted using Kanthal wire heaters. The validated model was also used to fill the experimental gaps by predicting the onset temperature for TR in simulated EV-ARC environment, heat generation rate due to different abuse reactions, the influence of heating power and heating arrangement as well as the effect of heat dissipation on TR evolution and the implications for battery thermal management. The present study has identified the TR onset temperature of the considered 21700 LIB to be between 131 and 132 °C. The predicted heat generation rate due to the decompositions of SEI and anode were found to follow similar patterns while that from cathode increase sharply near the maximum cell surface temperature, indicating the possibility of delaying TR onset temperature by optimising the cathode material. The time to maximum cell surface temperature decreases rapidly with the increase of the heating power.